Photoinduced charge separation in organic-organic heterojunctions based on porphyrin electropolymers. Spectral and time dependent surface photovoltage study - Durantini, Javier Esteban (2015)
Photoactive heterojunctions formed by porphyrin polymers were electrochemically generated and analyzed by both transient and spectral dependent surface photovoltage. Indium tin oxide/organic polymer heterojunction photovoltages showed to be dependent on the presence of Zn (II) as central metal on the porphyrin polymer structure. The porphyrin electropolymers were also successfully formed on the top of a poly 3,4-ethylenedioxythiophene layer, generated by electropolymerization. The presence of the hole transport polymer dramatically altered the formation and diffusion process of the photocarriers created by excitation of the porphyrin films. A marked increase in the generated photovoltages was observed when the porphyrin electropolymer external surfaces were modified with a layer of a strong electron acceptor (C60 buckminsterfullerene), showing that these heterojunctions could be used in the development of new solar energy technologies.